Polysomnographic Sleep and Circadian Temperature Rhythms as a Function of Prior Shift Work Exposure in Retired Seniors - Monk, Timothy H. (2013)
In an earlier published telephone interview study (n > 1,000) we have shown that retired shift workers subjectively report worse sleep than retired day workers. This laboratory study sought to determine whether these findings held up when objective polysomnograhic (PSG) measures of sleep were taken and whether retirees' circadian temperature rhythms differed as a function of shift work exposure. All completers of the telephone interview were invited to attend a 36-hour laboratory study for which participants were paid. This involved continuous core body temperature measurement (using an ingestible pill-based system) and 2 nights of PSG. Shift work exposure (plus other measures) was collected by taking a detailed work history. The second laboratory night was scored into sleep stages. Post hoc, we divided participants into 4 shift work exposure groups: 0 years (ie, no exposure to shift work), 1 to 7 years, 7 to 20 years, and >20 years. Sample sizes were 11, 16, 15, and 15, respectively, with approximate equality in mean age (71.7 years of age, 69.1 years of age, 70.0 years of age, and 70.4 years of age, respectively) and percent male (63%, 50%, 67%, and 73%, respectively). Shift work exposure was associated with worse PSG sleep in a dose-related fashion. The percentages of participants with sleep efficiency, 80% for the 0 years, 1 to 7 years, 7 to 20 years, and >20 years groups were 36%, 63%, 67%, and 73%, respectively (P < 0.01), and the percentages with total sleep time (TST), 6 hours were 36%, 56%, 53%, and 73%, respectively (P < 0.01). From the circadian rhythm record, shift work exposure appeared to result (P = 0.06) in an increased spread of phase angles (difference between habitual bedtime and time of temperature trough). In conclusion, it appears likely that shift work may be related to a scarring of sleep and circadian rhythms. This may be associated with a change in the relationship between habitual sleep timing and the phase of the circadian pacemaker.